Using Multi Criteria Decision-Making techniques to identify landfill sites: A Case study Al-Garraf Qadhaa, Dhi Qar, Iraq - Mukhalad N. Altai; Wassan A. Hassan; Faisel G. Mohammed; Ebtesam F. Khanjer; Sundus A. Abdullah Albakry; Ban A. Alrazaq (Genius Journals, 2024)
Located in the northern region of the Dhi Qar Governorate in southern Iraq, Al-Gharraf city boasts a population of approximately 117,549 inhabitants and encompasses an area spanning 623 square kilometers. The primary predicament afflicting residential areas within Al-Gharraf city is the absence of designated spaces for waste disposal. To mitigate this issue, a suitable waste disposal site was carefully chosen through the amalgamation of Geographic Information Systems (GIS) and a Multi-Criteria Decision-Making (MCDM) mechanism. A total of fifteen distinct criteria were considered, encompassing factors such as groundwater depth, urban centers, rivers, villages, schools, roads, elevation, slope, power plants, water surface, land use, gas pipelines, power lines, oil pipelines, and wells., were considered to ensure that the chosen site met all environmental, health, and economic requirements. Two decision-making methods "Analytic Hierarchy Process (AHP) and simple Additive Weighting (SAW)", The "weighted linear combination" (WLC) method was used to obtain a suitable spatial fit map, where this method was used for the process of deriving "weights using pairwise comparisons. Two suitable sites have been proposed for landfilling, and these sites meet all environmental, health and economic requirements and standards, according to the opinion of experts
Keywords: Geographic information system; landfill sites; Analytic Hierarchy Process